Effect of proximity to and view of, environmental land uses on property prices - A multidisciplinary review - Mittal, Jay; Byahut, Sweta (AESOP, 2016)
This paper provides a cross-disciplinary literature review of ‘proximity to’ and ‘view of’ eight different environmental amenity types on neighboring real property prices. The objectives of this paper are manifolds: first, it provides a comprehensive review of over 100 hedonic studies from five disciplines to understand variations in the marginal implicit price paid for homes near environmental amenities and how it differs from one amenity type to another? Second, this paper also identifies two most commonly used value capturing measurement variables, ‘proximity to,’ and ‘view of,’ amenities including their variants as used in the past hedonic studies (Mittal 2014). The appropriateness of variants used varies by the amenity type and its characteristics. This paper also presents analysis of characteristics similarities and differences amongst these eight amenity types explaining ‘why’ and ‘how much’ does the effect on property price varies across amenities and which variant of the two variables is most suited. This is the first attempt to compile a comprehensive review of literature from five disciplines across eight amenity types and provides a useful base for scholars interested in the topic. This review provides a useful insight to urban planners, real estate professionals and appraisers in understanding a range and variation in the marginal implicit price paid across environmental amenities.
Proceedings of the IV World Planning Schools Congress, July 3-8th, 2016 : Global crisis, planning and challenges to spatial justice in the north and in the south